Loan Forgiveness and Repayment: Can They Increase Education Attainment in Maine? - Reilly, Catherine (Maine Policy Review, 2005)
Maine’s level of higher education attainment has remained stubbornly low despite substantial efforts to improve the access to and availability of higher education options. Maine’s state economist, Catherine Reilly, examines the pros and cons of two perhaps underutilized policy tools for increasing Maine’s higher education attainment level—loan forgiveness and loan repayment. The design and marketing of such programs are critical, and would have to be done carefully. Reilly notes, however, that loan forgiveness and repayment are unique policy tools because they create incentives for students to live and work in the state after graduation.
Keywords: Maine; college loans; loan forgiveness